Synthesis and exploration of resorcinol derivatives as Plasmodium falciparum Hsp90 inhibitors - Umumararungu, Théoneste (Rhodes University, Faculty of Pharmacy, Pharmacy, 2016)
In this research project, we have synthesized a series of nine dimethyl ether resorcinol analogues of NMS-E973 (L-1) 38, a potent Hsp90 inhibitor. These analogues were chosen because they share the same pharmacophore with NMS-E973 (L-1) 38 and were thus expected to have a similar biological activity. Moreover, it is generally easier to synthesize the dimethyl ether resorcinol analogues of NMS-E973 (L-1) 38 as compared to their demethylated counterparts. Since other Hsp90 inhibitors such as geldanamycin 19 have demonstrated anti-plasmodial activity, we also expected our compounds to be Hsp90 inhibitors and to possess anti-plasmodial activity. However, our compounds were tested for growth inhibitory activity of Plasmodium falciparum and not for P. falciparum Hsp90 (PfHSP90) inhibitory activity. The synthesis involved a series of steps that led to the formation of the ester compound TU-011 (L-7) 43 that was then used as a precursor for different NMS-E973 (L-1) 38 analogues. The choice of analogues to be synthesized was dictated by binding affinity predictions obtained from molecular docking. The chosen synthetic analogues were active against chloroquine-sensitive Plasmodium falciparum (3D7 strain) in a Plasmodium lactate dehydrogenase assay and they were not generally cytotoxic to human cervical adenocarcinoma cell line HeLa. The most active of our compounds was TU-018 (L-103) 50 with an IC50 value of approximately 1.830 µM as compared to the standard, chloroquine, with an IC50 value of 0.01062 µM. Some of the compounds showed mild cytotoxicity towards HeLa cells with IC50 values higher than 25 µM as compared to the standard apoptosis inducer drug, emetine that had an IC50 value of 0.09948 µM. These results highlight the fact that the synthesized analogues are novel relatively non-toxic anti-plasmodial agents.
Keywords: Uncatalogued